L-Asparaginase from Penicillium sizovae Produced by a Recombinant Komagataella phaffii Strain - Marcela Freitas; Paula Souza; Mauricio Homem-; Yris M. Fonseca-Bazzo; Damaris Silveira; Edivaldo X. Ferreira Filho; Adalberto Pessoa Junior; Dipak Sarker; David Timson; João Inácio; Pérola O. Magalhães (MDPI AG, 2022)
L-asparaginase is an important enzyme in the pharmaceutical field used as treatment for acute lymphoblastic leukemia due to its ability to hydrolyze L-asparagine, an essential amino acid synthesized by normal cells, but not by neoplastic cells. Adverse effects of L-asparaginase formulations are associated with its glutaminase activity and bacterial origin; therefore, it is important to find new sources of L-asparaginase produced by eukaryotic microorganisms with low glutaminase activity. This work aimed to identify the L-asparaginase gene sequence from Penicillium sizovae, a filamentous fungus isolated from the Brazilian Savanna (Cerrado) soil with low glutaminase activity, and to biosynthesize higher yields of this enzyme in the yeast Komagataella phaffii. The L-asparaginase gene sequence of P. sizovae was identified by homology to L-asparaginases from species of Penicillium of the section Citrina: P. citrinum and P. steckii. Partial L-asparaginase from P. sizovae, lacking the periplasmic signaling sequence, was cloned, and expressed intracellularly with highest enzymatic activity achieved by a MUT+ clone cultured in BMM expression medium; a value 5-fold greater than that obtained by native L-asparaginase in P. sizovae cells. To the best of our knowledge, this is the first literature report of the heterologous production of an L-asparaginase from a filamentous fungus by a yeast.